SUSTAINABLE TECHNOLOGICAL DEVELOPMENT: A CHALLENGE IN BUSINESS INCUBATORS IN BRAZIL - Maia, Vagner Luiz; Barfknecht, Luciano; Scamati, Vagner; Pereira, Ricardo Aparecido (Seven Editora, 2025)
This article aims to analyze and understand technological development supported by sustainability in business incubators through a systematic literature review (SLR). The Sustainable Development Goals (SDGs) were developed by the United Nations (UN) as an important guiding tool for society. Business incubators play an important role in a local ecosystem to foster new ideas and promote the important mission of development with the lowest possible environmental impact. However, it is clear that technological development impacts on relevant gaps regarding the construction of sustainable and healthy environments applied to society. This work seeks to answer the question in a multidisciplinary way: what are the challenges encountered in sustainable technological development in Brazilian business incubators? The results point to the great potential of incubators to promote technological development with less environmental impact, however several limitations still prevent this process from occurring in an ideal way.DOI: https://doi.org/10.56238/sevened2025.029-037